Proximal femur fractures in COVID-19 emergency: the experience of two Orthopedics and Traumatology Departments in the first eight weeks of the Italian epidemic - Maniscalco, Pietro; Poggiali, Erika; Quattrini, Fabrizio; Ciatti, Corrado; Magnacavallo, Andrea; Vercelli, Andrea; Domenichini, Marco; Vaienti, Enrico; Pogliacomi, Francesco; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Introduction: CoVID-19 (Coronavirus disease) is a worldwide infection which is causing millions of deaths. A significant number of elderly patients require hospitalization and develop serious and sometimes life-threatening complications. The aim of this study is to evaluate the preliminary impact (8 weeks) of CoVID-19, focusing on proximal femur fractures, analyzing data and results compared to the same period of 2019. Materials and methods: From February 22nd to April 18th, 2020 we surgically treated 121 proximal femur fractures (61 in Piacenza; 60 in Parma, 16 male, 44 female, mean age 81.1). In the same period of 2019, we treated 169 proximal femur fractures (90 in Piacenza, 33 male, 57 female, mean age 81.9; 79 in Parma, 29 males, 50 female, mean age 80.2). We had 21/61 (34.4%) patients resulted positive for COVID-19 and 11/61 in Parma (18.3%), based on nasal-pharyngeal swab, chest CT scan and/or lung US findings. Results: The incidence of proximal femur fractures had a significant reduction during CoVID-19 spread in Piacenza and Parma. Authors have noticed an elevated number of deaths within 21 days after surgery. Piacenza: 4 cases in 2019 (4.4%) and 11 in 2020 (18.0%), of which 9 cases CoVID positive. In Parma in 2019 two deaths were encountered; in 2020 6 patients died and 5 cases were CoVID positive. Conclusion: In the first two months of the Italian epidemic, in the cities of Piacenza and Parma over 80% of deaths have occurred in patients over 70 years old. Even if preliminary, our study shows a significant increase in death in elderly patients surgically treated for proximal femur fractures, particularly in the Piacenza Hospital.